Influence of fibrosis progression on the viscous properties of in vivo liver tissue elucidated by shear wave dispersion in multifrequency MR elastography - Reiter, Rolf; Shahryari, Mehrgan; Tzschaetzsch, Heiko; Haas, Matthias; Bayerl, Christian; Siegmund, Britta; Hamm, Bernd; Asbach, Patrick; Braun, Juergen; Sack, Ingolf (Journal of the Mechanical Behavior of Biomedical Materials, 2021)
Purpose: Many elastography studies have shown that liver stiffness increases with fibrosis and thus can be used as a reliable marker for noninvasively staging fibrosis. However, the sensitivity of viscosity-related mechanical parameters, such as shear wave dispersion, to liver fibrosis is less well understood. Methods: In this proof-of-concept study, 15 healthy volunteers and 37 patients with chronic liver disease and biopsy-proven fibrosis were prospectively investigated by MR elastography at six drive frequencies of 35–60 Hz. Maps of shear wave speed (SWS, in m/s) and loss angle (φ, in rad), as a marker of stiffness and viscous properties, respectively, were generated using tomoelastography data processing. The Child-Pugh score was used to assess cirrhosis severity. Results: While SWS increased with fibrosis (F0: 1.53 ± 0.11 m/s, F1–F3: 1.71 ± 0.17 m/s, F4: 2.50 ± 0.39 m/s; P < 0.001), φ remained unchanged during mild to severe fibrosis (F0: 0.63 ± 0.05 rad, F1–F3: 0.60 ± 0.05 rad, P = 0.21) but increased in cirrhosis (F4: 0.81 ± 0.16 rad; P < 0.001). Correspondingly, the slope of SWS-dispersion within the investigated range of vibration frequencies increased from insignificant (F0–F3: 0.010 ± 0.007 m/s/Hz) to significant (F4: 0.038 ± 0.025 m/s/Hz; P = 0.005). Significant correlation with the Child-Pugh score was found for φ (R = 0.60, P = 0.01) but not for SWS. Conclusion: Although cirrhosis is associated with liver stiffening and, intuitively, transition towards more rigid material properties, the observed increases in φ and slope of SWS-dispersion indicate abnormally high mechanical friction in cirrhotic livers. This biophysical signature might provide a prognostic imaging marker for the detection of pathological processes associated with fibrosis independent of stiffness.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Cirrhosis; Fibrosis; Liver; Loss angle; MR Elastography; Viscoelasticity